Increase of depression among children and adolescents after the onset of the COVID-19 pandemic in Europe: a systematic review and meta-analysis - Ludwig-Walz, Helena; Dannheim, Indra; Pfadenhauer, Lisa Maria; Fegert, Jörg M.; Bujard, Martin (Child and adolescent psychiatry and mental health, 2022)
Background: Research points to a high depression burden among youth during the COVID-19 pandemic; however, a lack of systematic evidence exists. We determine the change in depression symptoms among children and adolescents during COVID-19 compared to pre-pandemic baselines. By using country differences in pandemic-related restrictions and school closures in Europe as quasi-experimental design, we evaluate policy impacts on depression. Methods: In this systematic review and meta-analysis, following the PRISMA statement, we searched six databases (MEDLINE, EMBASE, PsycINFO, Cochrane Central, Web of Science, WHO COVID-19) using a peer-reviewed search string up until March 18, 2022 with citation tracking and grey literature searches. No limitations regarding language and effect measures existed. We included studies that compared (1) general depression symptoms or (2) clinically relevant depression rates in children and adolescents (& LE; 19 years) before and during the COVID-19 pandemic in Europe. The validated Oxford Stringency Index was used as indicator for pandemic-related restrictions. Screening for eligibility, extracting data from published reports and from unpublished data requested directly from study authors, assessing the study risk of bias and grading certainty of evidence using the GRADE approach, were all done in duplicate. Data were pooled in a random-effects model. PROSPERO: CRD42022303714. Results: Of 7,422 nonduplicate records, 22 studies with data from 868,634 participants pre-pandemic and 807,480 during pandemic, met full inclusion criteria. For the comparison of depression symptoms before and during the COVID-19 pandemic, moderate certainty of evidence was observed for general depression symptoms (standardized mean difference, 0.21 [95%CI, 0.12-0.30]; I-2 = 94%) and low certainty of evidence for clinically relevant depression rates (odds ratio, 1.36 [95%CI, 1.05-1.76]; I-2 = 95%) for total population. Increase in general depression symptoms was higher for male adolescents, whereas increase in clinically relevant depression rates was higher for females. Effect estimates were significantly higher when pandemic-related restrictions were more stringent or school closure occurred. Conclusion: An increase in depression symptoms occurred in a pre-pandemic vs. during-pandemic comparison within the COVID-19 pandemic, whereby pandemic-related restrictions (such as school closures) resulted in a considerable effect increase. Ensuring adequate supply of mental health recovery services and long-term monitoring is of high public health relevance.
Gesehen am 18.10.2023
Keywords: Europa; Metaanalyse; Kind; Depression; COVID-19